Fore/aft movement is adapted to gate seperation by elite alpine racers in slalom - Kipp, R. W.; Reid, R. C.; Gilgien, M.; Haugen, P.; Smith, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Fore/aft position and movement have been shown to be related to performance in slalom [1,2]. These studies were carried out on a relatively tight slalom course using gates set with 10 m separation. This follow-up study from the same day tested similar relationships for slalom turns through a more open course with 13 m distances between gates. Methods. The performances of 6 members of the Norwegian men`s Europa Cup team were analyzed through 2 complete turns during a 13 m slalom race simulation. Skier 3-D positions were determined from 4 panning cameras and calibration control points distributed near the course [3]. Utilizing the method of Schiefermüller [4], a local coordinate system (LCS) originating at the outside ankle joint center was defined at each point in time. Motion of the body center of mass in the LCS fore/aft direction was divided into fore and aft phases of positioning relative to the outside ankle joint and time normalized to the turn cycle. Fore and aft position data were separately integrated over time in the positive and negative portions of the turn cycle and were then divided by the percent of turn cycle which they represented. Finally, the forward values were divided by the aft values to create a fore/aft ratio where a value of 1 would indicate a symmetrical distribution of fore/aft positioning about the ankle joint center. Ratios greater than or less than 1 thus indicated positioning which was biased either forward or backward, respectively. These ratios were then correlated with performance time controlling for each skier`s entrance velocity. Results. The mean fore/aft ratio for the 13 m course was 1.27 ± 0.54. The partial correlation coefficient between the fore/aft ratio and performance time was 0.735 (p = 0.03). This follow-up study found that when the turns changed from 10 to 13 m, the fore/aft ratio decreased from 2.44 ± 1.41 to 1.27 ± 0.54, indicating that skiers, on average, were further back and more fore/aft symmetric on the 13 m course. A two tailed t-test, assuming unequal variances, between the previous 10 m fore/aft ratios [1] and the current 13 m fore/aft ratios yielded a p =.10. Discussion. Fore/aft positioning of a slalom skier has been shown to be significantly related to performance. The correlation between fore/aft ratio and performance time was significant and positive for both 10 and 13 m courses (r = 0.980 and 0.735 respectively). Fore/aft positioning graphs were observed to be differently shaped for the two courses with more constant, closer to centered positioning for the 13 m course. This may in part be due to the increased time available between turns (about 12%) allowing different strategies. References [1] Kipp et al. (2008) Med Sci Sport & Exer, 40(5), S1246. [2] Tjørhom et al. (2007). 4th Int Congress on Science and Skiing, 158. [3] Nachbauer et al. (1996). J Appl Biomech, 12, 104-115. [4] Schiefermüller et al. (2005). Science & Skiing III, Meyer & Meyer Sport, 172-185.